Identification and Characterization of Antibiotic-Resistant Bacterial Strains in Hospital Wastewater - Ali Hussein, Yasmeen; Abd AL Jabbar, Widad; Al-Aubaidy, Hayder (Journal of Biomedicine and Biochemistry, 2025)
Hospital wastewater systems are recognized as reservoirs for the emergence and dissemination of antibiotic-resistant bacteria. This study isolated bacterial strains from hospital effluents and assessed their resistance profiles using disk diffusion and minimum inhibitory concentration (MIC) methods. Molecular characterization via PCR and sequencing identified genes associated with resistance, including blaCTX-M, mecA, and vanA. High prevalence of multidrug-resistant strains such as MRSA and ESBL-producing Enterobacteriaceae was observed. These findings highlight the urgent need for improved wastewater treatment processes and strict antimicrobial stewardship to prevent environmental and public health risks.